2011
DOI: 10.1093/ejo/cjq192
|View full text |Cite
|
Sign up to set email alerts
|

Cervical vertebrae anomalies in subjects with Class II malocclusion assessed by lateral cephalogram and cone beam computed tomography

Abstract: A high prevalence of cervical vertebrae anomalies (CVA) has been recently associated with various malocclusions. Our aim was to study the prevalence of CVA on lateral cephalograms in Class II subjects and to compare the findings with those obtained from cone beam computed tomography (CBCT). Standardized cephalograms of 238 Class II patients were analysed for CVA. Cephalogram and CBCT were available for an additional 21 subjects. Cephalometric values were correlated with vertebrae morphology; logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…21,22 In the present study, in order to avoid 'pseudofusion,' fusion was only registered if fusion was found consistently on all consecutive lateral cephalograms of the same patient and if fusion was confirmed independently by two of the authors. In a recent study 22 it was found that the agreement between lateral cephalograms and cone-beam computed tomographic images in detecting upper spine deviations was good and that lateral cephalograms were sufficient for evaluating the upper spine morphology.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In the present study, in order to avoid 'pseudofusion,' fusion was only registered if fusion was found consistently on all consecutive lateral cephalograms of the same patient and if fusion was confirmed independently by two of the authors. In a recent study 22 it was found that the agreement between lateral cephalograms and cone-beam computed tomographic images in detecting upper spine deviations was good and that lateral cephalograms were sufficient for evaluating the upper spine morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that some fusions observed on 2D radiographs were more likely to be pseudofusions. [25][26][27] Oblique These studies have recommended a more valid method such as 3D radiographs (CT or CBCT) for assessing fusions. In the present study, no statistically significant differences in the occurrence of morphological deviations of the cervical column were found between lateral cephalograms and CBCT images, and the agreement was k 5 0.64.…”
Section: Discussionmentioning
confidence: 99%
“…24 The difficulty of reliably determining morphological deviations in the cervical vertebral column on a single lateral cephalogram has been discussed in the literature. [25][26][27] Studies have found that some fusions observed on 2D radiographs were more likely to be "pseudofusions", and that a more valid method such as three-dimensional (3D) radiographs [CT or cone beam CT (CBCT)] is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…(2) However, according to previous studies, the facial morphology affects the morphology of cervical vertebrae. (1,(3)(4)(5) Of other factors that can affect both facial and cervical postures is the res-piratory needs. (4,(6)(7)(8) Solow et al, (6) Wenzel et al, (7) and Chen et al (8) reported a correlation between the respiratory needs and the head position.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Previous studies have confirmed the impact of vertical and sagittal parameters of the craniofacial system on the morphology of cervical vertebrae. (1,3,5,9,10) Unfortunately, although some studies have been conducted to evaluate the relation-ship between the facial morphology and the cervical vertebral morphology, the possibility of any correlation between pathological problems associated with cervical vertebral fusion and long facial pattern has been limitedly assessed. The aim of the present study was to determine the correlation between cervical vertebral fusion and long facial pattern in adults.…”
Section: Introductionmentioning
confidence: 99%